PENGOLAHAN KUE KASTENGEL IKAN TUNA DI DESA SAMPULUNGAN - Rapi, Nuraeni L; Cahyono, Indra; Kantun, Wayan; Harianti, Harianti; Karim, Mutemainna; Muchtar, Muthahharah (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2023)
The variety of processed fish products is very important to increase the selling value and standard of consumer tastes so as not to cause a feeling of saturation with pre-existing products. One of processed fish products is kastengel cake. The aim is to provide the knowledge and skills of fishermen's wives in processing fishery products into kastengel cakes. The method used in service activities is counseling and direct practice. Counseling on the production of tuna nuggets was held on Thursday, 20 November 2022 in Sampulangan Village, Takalar Regency. The results of the activity are processed tuna fish products, namely kastengel cakes with high taste and nutritional value.